MyEduTechApp® - Farrah Dina, Y.; Rafiza , A.R. (University of Malaya, 2014)
Mobile computing devices such as iPad, tablet computers, netbooks, and smartphones have become a social phenomenon in today’s society. Whilst there are thousands of apps available in the market today, choosing the most appropriate ones for children to use and play with is problematic. This is because some of the apps such as games-based apps are very entertainment-oriented and lack of its educational impact on child cognitive and attitude development. Moreover, some apps are unsuitable for the specific age of the children which may result in issue with content appropriateness or to some extent graphic appropriateness. Violent games, for instance, do not have much, if not any, educational values for children to learn from and are definitely unsuitable for younger children. This app will help parents and educators in choosing suitable mobile educational apps for children from birth to 12 years old. Selection of the apps is based on the theory of Multiple Intelligences (Howard Gardner, 1993) The trademark registered in class 41